The Promise of the Dual Prevention Pill: A Framework for Development and Introduction - Friedland, Barbara A.; Mathur, Sanyukta; Haddad, Lisa B. (Frontiers in Reproductive Health, 2021)
Women of reproductive age need multipurpose prevention technology (MPT) products to address two overlapping health risks: unintended pregnancy and sexually transmitted infections (STIs), including HIV. Currently, condoms are the only available MPT, yet male condoms are not within a woman’s control, and uptake of female condoms has been limited by low acceptability and cost. Women globally need more options for HIV and pregnancy prevention. Several MPTs for simultaneous HIV and pregnancy prevention are in various stages of development and clinical testing, yet likely many years away from market launch. A dual prevention pill (DPP) combining oral contraceptives and oral pre-exposure prophylaxis, both of which are licensed, approved products in many low and middle-income countries (LMICs), is likely to be the fastest route to getting an MPT product into women’s hands. The successful roll-out of the DPP will require careful consideration of user-, provider-, and product-centered factors during product development and introduction. Early attention to these inter-related factors can help ensure that the DPP has the ideal characteristics for maximum product acceptability, that effective and quality services are designed and implemented, and that users are able to make informed choices, demand the product, and use it effectively. Our proposed framework outlines key consideration for the effective development and introduction of the DPP, which could also facilitate integration models for future MPTs.